2017
DOI: 10.1016/j.jsams.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Exercise intensity, redox homeostasis and inflammation in type 2 diabetes mellitus

Abstract: Objectives: To compare 12 weeks of exercise training at two intensities on oxidative stress, antioxidants and inflammatory biomarkers in patients with type 2 diabetes (T2D). Design: Randomized trialMethods: Thirty-six participants with T2D were randomized to complete either 12 weeks of treadmill based high-intensity interval training (HIIT) or moderate-intensity continuous training (MICT), followed by 40 weeks of home-based training at the same intensities. Plasma inflammation, oxidative stress and antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 27 publications
4
54
0
Order By: Relevance
“…However, currently, no studies have comprehensively examined the effect of HIIT on inflammatory cytokines and adipokines 34,38 for which effects have been mixed. [39][40][41][42] Therefore, the aim of this meta-analysis was to assess the impact of HIIT on inflammatory cytokine and adipokines in individuals with metabolic disorders, together with the modulatory effects of the training protocol and the participants physiological characteristics.…”
mentioning
confidence: 99%
“…However, currently, no studies have comprehensively examined the effect of HIIT on inflammatory cytokines and adipokines 34,38 for which effects have been mixed. [39][40][41][42] Therefore, the aim of this meta-analysis was to assess the impact of HIIT on inflammatory cytokine and adipokines in individuals with metabolic disorders, together with the modulatory effects of the training protocol and the participants physiological characteristics.…”
mentioning
confidence: 99%
“…The fact that the selected papers for this review have found results different from the others may be associated then, according to Brun et al 26 and Krousel et al, 27 to the use of low intensity interventions, low volume or low compliance to intervention being the study of Mallard et al, 16 the only one to use training of moderate and intense intensities. These authors report that both MICT (Moderate Intensity Continuous Training) and HIIT (High Intensity Interval Training) had no effect on oxidative stress and inflammatory levels in individuals with T2DM over the 12 weeks of intervention with one year follow-up.…”
Section: Discussionmentioning
confidence: 93%
“…In the study by Mallard et al, 16 36 participants with T2DM were allocated into two groups in a randomized, HIIT (High Intensity Interval Training) or MICT (Moderate Intensity Continuous Training) group, through of a parallel design. Participants completed the first phase of 12 weeks of specific intensity physical training with a combination of supervised and home training.…”
Section: St Author Local / Year Sample / Age Design Of the Study Meamentioning
confidence: 99%
“…In our investigation, both the MCT and HIIT combined with RT regimens reduced the circulating levels of IL-6 following 1-year of exercise when compared with the control group, whereas no results were observed for the remaining in ammatory markers. The number of investigations that have analysed the impact of HIIT on the in ammatory pro le in T2DM are scarce, with only two shortterm interventions (< 12-week duration) reporting no substantial effects on IL-6, TNF-α, and CRP (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…However, the same review suggested that there was no consensus on the long-term effects of HIIT, nor the effectiveness of HIIT vs. MCT on lipid pro le in individuals with T2DM, mainly owing to the inexistence of longer interventions or the reduced number of randomized control trials (RCT) analysing both protocols. As far as the in ammatory pro le goes, just two non RCTs analysed the impact of HIIT in individuals with T2DM, with both having a short duration intervention (< 12-weeks) and with the results suggesting limited impact (16,17).…”
mentioning
confidence: 99%